An innovative compound that promotes oral wound healing via mobilizing gingival mesenchymal stem cell homing - Lei Yang; Yue Song; Yao Jiao; Siyan Liu; Yi Liu; Lijia Guo; Yitong Liu (Biochemistry and Biophysics Reports, 2025)
Oral wound healing is a complex biological process involving inflammation, proliferation, and tissue remodeling. Gingival mesenchymal stem cells (GMSCs) play a crucial role in this process due to their regenerative potential and immunomodulatory properties. This study investigated whether Purpurolide C (PC), a fungal-derived bioactive compound, could promote oral wound healing by promoting the migratory ability of GMSCs. In vitro, PC enhanced GMSC migration, pluripotency, and osteogenic differentiation. In vivo, a mouse palatal soft tissue defect model demonstrated that PC significantly accelerated wound closure and increased GMSC recruitment to the wound site. Furthermore, 16S rRNA sequencing revealed that PC administration did not disrupt gut microbiota homeostasis. These findings suggest that PC is a promising therapeutic agent for enhancing oral wound healing, paving the way for potential clinical applications in regenerative medicine.